Djibouti : First Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2004)
This paper on the First Review Under the Staff-Monitored Program (SMP) on Djibouti explains macroeconomic framework and policies. The policy discussions centered on the need to sustain the improvement in the country's fiscal position in the remainder of the year and steadfast structural reforms to create the basis for sustainable growth. Determined efforts by the authorities are needed to implement the longstanding structural reforms planned under the SMP. IMF staff recognizes the difficulties in adopting a challenging reform agenda and the need to achieve a political consensus.